Gustatory responsiveness in Vespula germanica workers: exploring the interplay between sensory perception and task specialization - Mattiacci, Analia (2023)
Workers’ task specialization and division of labor are critical features of social insects’ ecological success. It has been proposed that the division of labor relies on response threshold models: individuals varying their sensitivity (and responsiveness) to biologically relevant stimuli and performing a specific task when a stimulus exceeds an internal threshold. In this work, we study carbohydrate and protein responsiveness and their relation to worker task specialization in Vespula germanica, an invasive social wasp. The sucrose and peptone responsiveness of two different subcastes, preforagers and foragers, was determined by stimulating the antenna of the wasps with increasing concentrations of the solution and quantifying whether each concentration elicited a licking response. We studied responsiveness in five different ways: (1) response threshold, (2) concentration 50 (concentration to which at least 50% of wasps responded), (3) maximum response, (4) mean scores and (5) median scores. Our results suggest that V. germanica foragers are more sensitive to sucrose (lower thresholds) than preforager workers. However, we found no differences for peptone thresholds (i.e., a protein resource). Nonetheless, this is the first study to investigate response thresholds for protein resources. The intercaste variation in sucrose responsiveness shown in our work contributes to the existing knowledge about response threshold theory as a mechanism for task specialization observed in V. germanica.